# |
ODE |
Mathematica |
Maple |
\[
{}\left (2 x -1\right ) y^{\prime \prime }-\left (3 x -4\right ) y^{\prime }+\left (x -3\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }-\left (x +a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+2 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+4 y^{\prime }-\left (x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+4 y-\left (x +2\right ) y+l y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+4 m y^{\prime }-\left (x -2 m -4 n \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}16 x y^{\prime \prime }+8 y^{\prime }-\left (x +a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}a x y^{\prime \prime }+b y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}a x y^{\prime \prime }+\left (b x +3 a \right ) y^{\prime }+3 b y = 0
\] |
✓ |
✓ |
|
\[
{}5 \left (a x +b \right ) y^{\prime \prime }+8 a y^{\prime }+c \left (a x +b \right )^{{1}/{5}} y = 0
\] |
✓ |
✓ |
|
\[
{}2 a x y^{\prime \prime }+\left (b x +a \right ) y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}2 a x y^{\prime \prime }+\left (b x +3 a \right ) y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}\left (\operatorname {a2} x +\operatorname {b2} \right ) y^{\prime \prime }+\left (\operatorname {a1} x +\operatorname {b1} \right ) y^{\prime }+\left (\operatorname {a0} x +\operatorname {b0} \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a x +b \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-\left (a \,x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a^{2} x^{2}-6\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a \,x^{2}-v \left (v -1\right )\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a \,x^{2}+b x +c \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a \,x^{k}-b \left (b -1\right )\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+a y^{\prime }-x y = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }+a y^{\prime }-\left (b^{2} x^{2}+a b \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-\left (x +a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (-v^{2}+x^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (l \,x^{2}-v^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x +a \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+\left (a \,x^{m}+b \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }+\left (a x -b^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }+\left (a \,x^{2}+b \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }+\left (l \,x^{2}+a x -n \left (n +1\right )\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 \left (x -1\right ) y^{\prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 \left (x +a \right ) y^{\prime }-b \left (b -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (a^{2} x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+5 x y^{\prime }-\left (2 x^{3}-4\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+a x y^{\prime }+b y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a x +b \right ) y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+a x y^{\prime }+\left (b \,x^{m}+c \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x^{2} y^{\prime }+\left (a x +b \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x^{2} y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x^{2}-1\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x \left (1+x \right ) y^{\prime }+\left (x -9\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x \left (1+x \right ) y^{\prime }+\left (3 x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x \left (x +3\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x \left (x -1\right ) y^{\prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-\left (x^{2}-2 x \right ) y^{\prime }-\left (x +a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-\left (x^{2}-2 x \right ) y^{\prime }-\left (3 x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x \left (x +4\right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x^{2} y^{\prime }-v \left (v -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x \left (2 x +1\right ) y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+2 \left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+a \,x^{2} y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a +2 b \right ) x^{2} y^{\prime }+\left (\left (a +b \right ) b \,x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+a \,x^{2} y^{\prime }+f \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }+\left (2 a x +b \right ) x y^{\prime }+\left (a b x +c \,x^{2}+d \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a x +b \right ) y^{\prime } x +\left (\operatorname {a1} \,x^{2}+\operatorname {b1} x +\operatorname {c1} \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x^{3} y^{\prime }+\left (x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x^{2}+2\right ) x y^{\prime }+\left (x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x \left (x^{2}-a \right ) y^{\prime }+\left (2 n \,x^{2}+\left (\left (-1\right )^{n}-1\right ) a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+4 x^{3} y^{\prime }+\left (4 x^{4}+2 x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a \,x^{2}+b \right ) x y^{\prime }+f \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x^{3}+1\right ) x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (-x^{4}+\left (2 n +2 a +1\right ) x^{2}+\left (-1\right )^{n} a -a^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a \,x^{n}+b \right ) y^{\prime } x +\left (\operatorname {a1} \,x^{2 n}+\operatorname {b1} \,x^{n}+\operatorname {c1} \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (a \,x^{\operatorname {a1}}+b \right ) x y^{\prime }+\left (A \,x^{2 \operatorname {a1}}+B \,x^{\operatorname {a1}}+C \,x^{\operatorname {b1}}+\operatorname {DD} \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }-\left (2 x^{2} \tan \left (x \right )-x \right ) y^{\prime }-\left (x \tan \left (x \right )+a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (2 x^{2} \cot \left (x \right )+x \right ) y^{\prime }+\left (x \cot \left (x \right )+a \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x f \left (x \right ) y^{\prime }+\left (f^{\prime }\left (x \right ) x +f \left (x \right )^{2}-f \left (x \right )+a \,x^{2}+b x +c \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x^{2} f \left (x \right ) y^{\prime }+\left (x^{2} \left (f^{\prime }\left (x \right )+f \left (x \right )^{2}+a \right )-v \left (v -1\right )\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+\left (x -2 x^{2} f \left (x \right )\right ) y^{\prime }+\left (x^{2} \left (1+f \left (x \right )^{2}-f^{\prime }\left (x \right )\right )-f \left (x \right ) x -v^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-v \left (v -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+3 x y^{\prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+a x y^{\prime }+\left (a -2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-v \left (v +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+x y^{\prime }+a y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+x y^{\prime }+f \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+2 x y^{\prime }-l y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+2 x y^{\prime }-v \left (v +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }-\left (v +2\right ) \left (v -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-\left (1+3 x \right ) y^{\prime }-\left (x^{2}-x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+2 \left (n +1\right ) x y^{\prime }-\left (v +n +1\right ) \left (v -n \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-2 \left (n -1\right ) x y^{\prime }-\left (v -n +1\right ) \left (v +n \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-2 \left (v -1\right ) x y^{\prime }-2 v y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+2 a x y^{\prime }+a \left (a -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+a x y^{\prime }+\left (b \,x^{2}+c x +d \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }+\left (a x +b \right ) y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-a^{2}+x^{2}\right ) y^{\prime \prime }+8 x y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|